The Elevated Susceptibility to Diabetes in India: An Evolutionary Perspective - Wells, Jonathan C. K.; Pomeroy, Emma; Walimbe, Subhash R.; Popkin, Barry M.; Yajnik, Chittaranjan S. (Frontiers in Public Health, 2016)
India has rapidly become a ‘diabetes capital’ of the world, despite maintaining high rates of under-nutrition. Indians develop diabetes at younger age and at lower body weights than other populations. Here, we interpret these characteristics in terms of a 'capacity-load' model of glucose homeostasis. Specifically, we assume that glycemic control depends on whether the body’s ‘metabolic capacity’, referring to traits such as pancreatic insulin production and muscle glucose clearance, is able to resolve the ‘metabolic load’ generated by high levels of body fat, high dietary glycemic load and sedentary behavior. We employ data from modern cohorts to support the model and the interpretation that elevated diabetic risk among Indian populations results from the high metabolic load imposed by westernized lifestyles acting on a baseline of low metabolic capacity. We attribute this low metabolic capacity to the low birth weight characteristic of Indian populations, which is associated with short stature and low lean mass in adult life. Using stature as a marker of metabolic capacity, we review archaeological and historical evidence to highlight long-term declines in Indian stature associated with adaptation to several ecological stresses. Underlying causes may include increasing population density following the emergence of agriculture, the spread of vegetarian diets, regular famines induced by monsoon failure, and the undermining of agricultural security during the colonial period. The reduced growth and thin physique that characterize Indian populations elevate susceptibility to truncal obesity, and increase the metabolic penalties arising from sedentary behavior and high glycaemic diets. Improving metabolic capacity may require multiple generations, in the meantime efforts to reduce the metabolic load will help ameliorate the situation.